The Role of Probiotics in Alleviating Postweaning Diarrhea in Piglets From the Perspective of Intestinal Barriers - Su, Weifa; Gong, Tao; Jiang, Zipeng; Lu, Zeqing; Wang, Yizhen (Frontiers in Cellular and Infection Microbiology, 2022)
Early weaning of piglets is an important strategy for improving the production efficiency of sows in modern intensive farming systems. However, due to multiple stressors such as physiological, environmental and social challenges, postweaning syndrome in piglets often occurs during early weaning period, and postweaning diarrhea (PWD) is a serious threat to piglet health, resulting in high mortality. Early weaning disrupts the intestinal barrier function of piglets, disturbs the homeostasis of gut microbiota, and destroys the intestinal chemical, mechanical and immunological barriers, which is one of the main causes of PWD in piglets. The traditional method of preventing PWD is to supplement piglet diet with antibiotics. However, the long-term overuse of antibiotics led to bacterial resistance, and antibiotics residues in animal products, threatening human health while causing dysbiosis of gut microbiota and superinfection of piglets. Antibiotic supplementation in livestock diets is prohibited in many countries and regions. Regarding this context, finding antibiotic alternatives to maintain piglet health at the critical weaning period becomes a real emergency. More and more studies showed that probiotics can prevent and treat PWD by regulating the intestinal barriers in recent years. Here, we review the research status of PWD-preventing and treating probiotics and discuss its potential mechanisms from the perspective of intestinal barriers (the intestinal microbial barrier, the intestinal chemical barrier, the intestinal mechanical barrier and the intestinal immunological barrier) in piglets.